CPLD-Based Displacement Measurement System for Nanoscale Grating Ruler - Jiyuan Sun; Chunlin Tian (Journal of Chemistry)
With the continuous development of science and technology, industrial production has higher and higher requirements for precision. Many high-precision measurement technologies emerge as the times require, and nanoscale grating ruler displacement measurement technology is one of them. As a kind of precision sensor, nanoscale grating ruler has important application in displacement measurement system. CPLD has the advantages of high integration and fast programming speed, which is often used to control the displacement measurement system of nanoscale grating ruler. The purpose of this paper is to deeply explore the measurement effect and related application principle of nanoscale grating ruler displacement measurement system based on CPLD technology. A set of nanoscale grating ruler displacement measurement system is designed based on CPLD technology. The output signal of grating ruler is programmed by CPLD. The x-axis displacement of the experimental platform controlled by stepping motor is measured, and the measured data are recorded by carrying out analysis and research. The results show that compared with the traditional phase difference measurement system, the measurement accuracy of the system based on CPLD is improved by 24.7%, the robustness of the measurement system is improved by 18.6%, and the measurement speed is increased by 27.3%. Therefore, this kind of nanoscale measurement precision grating ruler displacement measurement control system based on CPLD has three characteristics: high measurement accuracy, strong anti-interference ability, and high measurement motion efficiency, which can effectively meet the requirements of grating ruler displacement measurement system for high-precision manufacturing technology.